Pengaruh Jenis Mulsa dan Dosis Bokashi Terhadap Pertumbuhan Cabai Rawit (Capsicum frutescens L.) - Ahmad Raksun; Mahrus Mahrus; I Gde Mertha (Jurnal Penelitian Pendidikan IPA, 2020)
This research is about the effect of mulch type and bokashi dose on the growth of chili. This study aims to determine: (1) the effect of mulch type on the growth of chili, (2) the effect of bokashi dose on the growth of chili, (3) the effect of the interaction of mulch type and bokashi dose on the growth of chili. This research used factorial design consisting of 2 factors. The first factor is the type of mulch which consists of 3 types of mulch namely black silver plastic mulch, rice straw mulch and dry leaf mulch. The second factor is the dose of bokashi which consists of 6 levels, namely: Po = without giving bokashi (control), P1 = giving 0.4 kg bokashi, P2 = giving 0.8 kg bokashi, P3 = giving 1.2 kg of bokashi, P4 = giving 1.6 kg of bokashi and P5 = giving 2.0 kg of bokashi. Growth parameters measured were stem height, leaf blade length, leaf blade width and wet weight of chili stems. Data analysis was performed by analysis of variance. The results showed that: (1) mulch type significantly affected stem height, stem wet weight, leaf blade length and leaf blade width, silver black plastic mulch gave better results than other mulches, (2) The dose of organic fertilizer significantly affected height stem, stem wet weight and leaf blade length but not significantly affect leaf blade width, (3) interaction of mulch type and bokashi dose did not significantly affect stem height, stem weight, stem length, leaf blade length and leaf blade width